2008
DOI: 10.1074/jbc.m802557200
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Interaction of Botulinum Neurotoxin A Translocation (T) Domain

Abstract: The translocation of the catalytic domain through the membrane of the endosome to the cell cytoplasm is a key step of intoxication by botulinum neurotoxin (BoNT). This step is mediated by the translocation (T) domain upon endosome acidification, although the mechanism of interaction of the T domain with the membrane is still poorly understood. Using physicochemical approaches and spectroscopic methods, we studied the interaction of the BoNT/A T domain with the membrane as a function of pH. We found that the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
28
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 36 publications
5
28
0
Order By: Relevance
“…It is thought that the acidic pH of the endosome triggers HCT pore formation and LC translocation (6). In vitro studies have shown that BoNT (and the isolated BoNT HCT) undergoes pH-dependent membrane insertion and pore formation (7)(8)(9)(10)(11)(12)(13), and single molecule translocation events have been observed in excised patches of neuronal cells (14,15). These studies support a model in which the HCT acts as both a conduit and a chaperone for the transit of the LC protease across the membrane (5,11,16).…”
supporting
confidence: 60%
“…It is thought that the acidic pH of the endosome triggers HCT pore formation and LC translocation (6). In vitro studies have shown that BoNT (and the isolated BoNT HCT) undergoes pH-dependent membrane insertion and pore formation (7)(8)(9)(10)(11)(12)(13), and single molecule translocation events have been observed in excised patches of neuronal cells (14,15). These studies support a model in which the HCT acts as both a conduit and a chaperone for the transit of the LC protease across the membrane (5,11,16).…”
supporting
confidence: 60%
“…Cardiolipin has two phosphate groups, but it effectively behaves like it has one negative charge at physiological pH. It appears that the binding of H N 729 -845 is primarily aided by the negative charge on the head of the gangliosides or the lipid and is consistent with the findings of Galloux et al (48), where the membrane surface charges are reported to play an active role in the H N domain-membrane interaction. Involvement of the surface charge in interactions of H N 729 -845 with the cell explains the binding of the peptide to CHO-K1 and HEK-293T cells.…”
Section: Discussionsupporting
confidence: 80%
“…This was further supported by reports where the H N domain-L-chain framework was used as a secretion inhibitor by fusion to a new cell-targeting domain (45)(46)(47). Using physicochemical and spectroscopic methods, Galloux et al (48) found that the H N domain interacts with the membrane; however, the interaction did not involve major secondary or tertiary structural changes. Below its pI of 5.5, the H N domain becomes insoluble and is capable of penetrating lipid vesicles.…”
Section: Discussionsupporting
confidence: 53%
“…The identity of the protein receptor for BoNT/C remains to be established. Upon SV endocytosis, the drop in luminal pH triggers the transformation of the HC into a translocation machine (Fischer, 2013, Montal, 2010, Williamson and Neale, 1994, Fu et al, 2002, Puhar et al, 2004, Galloux et al, 2008, Pirazzini et al, 2013); interestingly, the ability to sense low pH requires the interaction of the HC with the ganglioside co-receptor (Sun et al, 2011). The HC then translocates the LC into the cytosol, where it cleaves neuronal soluble N- ethylmaleimide attachment receptors (SNAREs), which form the core of a conserved membrane fusion complex (Rothman, 1994).…”
Section: Introductionmentioning
confidence: 99%